DISCOURSE OF POWER AND DISCOURSE OF MASSES IN MODERN PHILOSOPHICAL ANTHROPOLOGY: CULTURAL, BIOLOGICAL AND RELIGIOUS DIMENSIONS - Karpenko, S. R. (Anthropological Measurements of Philosophical Research, 2015)
The aim of the paper is the identification of anthropological content of the power and mass discourses in contemporary social transformations. The theme of philosophical and anthropological meaning of discourse communication between mass and power in post-modern society acquires the significant relevance because of technologization of the governance processes and transformation of previously sacred power as a set of standard procedures. Methodology of the paper consists on the disclosure of cultural peculiarities and substantial forms of power discourse and mass discourse properties in major directions of philosophical anthropology of middle XX and at the beginning of the XXI century. Scientific novelty. The directions of the institutional sense expression in the discourse of power supply are disclosed and the process of mixing power and management and representative anthropology is fixed. The biological, cultural and religious levels of displaying the anthropological significance discourse of power are identified. The definition is given to the anthropic content of discursive power of speech activities and methods and philosophical reflection of the discursive self-expression of powerful masses. The specificity of the interaction of power and mass discourses of national and universal semantic spaces are defined. In conclusions it is indicated that the anthropic space of the contemporary mass human is narrowing significantly, because the individuals’ participation in technology of society management is finally excluded. On this basis even the key aspect of mass discourse breaks – the mass narrations about the power, because the power performs the direct intervention in the mass discourse structure of sense-creation by the way of suggestion.